Effects of infiltration characteristics on slope stability - Lee, Daryl Tsen-Tieng. (2008)
This thesis presents a study on the infiltration characteristics of a residual soil slope made up of soil from the Jurong Sedimentary Formation in Singapore. The study was made up of fieldwork, laboratory tests and computer modeling. The fieldwork was conducted using rainfall simulations, natural rainfall measurements, runoff measurements, pore-water pressure measurements and time domain reflectometry measurements of volumetric water contents. The laboratory work consisted of pressure plate tests and falling head saturated permeability tests. The computer modeling work was made up of a parametric study conducted using the program SEEP/W.